(untitled) (Journal of Guidance and Counselling Studies, 2024)
This paper delved on psychological strategies for minimizing youth restiveness and their implication on national security. The conceptual definitions of youth, restiveness, youth restiveness, and national security have been provided in the paper. The causes of youth restiveness which include poor governmental policies, lack of access to quality and functional education, decay in infrastructural facilities, lack of job opportunities, poor standard of living, and absence of communication network have been discussed. The paper has also analyzed the psychological strategies for minimizing youth restiveness in the society. These include use of cognitive behavioural therapy, provision of positive reinforcement, mindfulness meditation, self-regulation techniques, groupcounselling methods, parental involvement, social support, role modeling, and community engagement. The paper has further discussed the implications of youth restiveness on national security which includes increased criminal activities, uncertainty or anxiety, economic sabotage, underdevelopment, agitation and rebelliousness, and cybercrimes. The paper has recommended provision of quality and functional education through basic education and literacy programmes, establishment of skill acquisition centres, job creation through infrastructural development, people oriented economic policies for improved standard of living, and value re-orientation, among others.